2018
DOI: 10.26444/aaem/75422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of trace metals in follicular fluid in ICSI-treated patients

Abstract: This study investigated the influence of cadmium (Cd), copper (Cu), iron (Fe), lead (Pb), selenium (Se), and zinc (Zn) in follicular fluid on the effectiveness of in vitro fertilization (IVF) treatment and the dynamics of embryo development. The study involved 221 women aged 25-35 years in whom intracytoplasmic sperm injection (ICSI) was performed. Analysis of the effects of the average concentrations of Se, Zn, and Cu on the developmental dynamics of embryos showed that higher concentrations of these metals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
(35 reference statements)
2
22
2
Order By: Relevance
“…In fact, a study of reproductive age women using a nationally representative 2013–2016 US data set, reported a non-linear dose–response association for blood Hg concentrations and clinical infertility, with a threshold of ∼5.3 µg/l ( Zhu et al , 2020 ). Our results are particularly concerning given that the FF Hg ( Al-Saleh et al , 2008 ; Bloom et al , 2012b ; Tolunay et al , 2016 ) and Pb ( Paksy et al , 2001 ; Silberstein et al , 2004 ; Al-Saleh et al , 2008 ; Bloom et al , 2012b ; Tolunay et al , 2016 ; Wdowiak et al , 2018 ) concentrations in our study population are lower than reported by other studies.…”
Section: Discussioncontrasting
confidence: 73%
“…In fact, a study of reproductive age women using a nationally representative 2013–2016 US data set, reported a non-linear dose–response association for blood Hg concentrations and clinical infertility, with a threshold of ∼5.3 µg/l ( Zhu et al , 2020 ). Our results are particularly concerning given that the FF Hg ( Al-Saleh et al , 2008 ; Bloom et al , 2012b ; Tolunay et al , 2016 ) and Pb ( Paksy et al , 2001 ; Silberstein et al , 2004 ; Al-Saleh et al , 2008 ; Bloom et al , 2012b ; Tolunay et al , 2016 ; Wdowiak et al , 2018 ) concentrations in our study population are lower than reported by other studies.…”
Section: Discussioncontrasting
confidence: 73%
“…Contamination of the environment, especially air, water, and soil with heavy metals such as heavy metals, leads to an increase in heavy metals in food so that the presence of heavy metals in food is therefore inevitable. Plants and plant products, such as bread and cereals, fish and meat, are the most susceptible to contamination, Pb and Cd are the most recognized reproductive toxins human exposure to occupational and environmental pollutants, contributing to adverse effects on chromatin integrity (Wdowiak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the best recognized chemical agents which are attributable to the generation of oxidative stress, are indicated heavy metals, air pollution, plant protection products and tobacco smoke [4,5,6,7]. The physical factors responsible for inducing this phenomenon are electromagnetic fields [8] and ionizing radiation (IR) [9].…”
Section: Introduction and Objectivementioning
confidence: 99%